The economic geography of the Union's chicory Industry : past and present - Young, Bruce Stratton (Rhodes University, Faculty of Science, Department of Geography, 1959)
The motivating force behind this survey and study of a branch of the Union's agricultural industry has been the conviction that detailed case studies of economic activities and their influences on the map of the country are the essential foundation stones on which mature scholars may build a perceptive and valuable economic geography of the Union.
Keywords: Chicory -- South Africa